The Use of Instructional Media to Improve Arabic Language Skills among Islamic Boarding School Students - Saadatu Mukkaromatil Arifah; Syamsidar binti Halim (IJIBS, 2025)
Arabic language learning in Islamic boarding schools often faces challenges, especially in developing students’ speaking skills One major factor is the limited use of varied instructional media, which can make learning monotonous and less engaging. This situation reduces students’ motivation, participation, and confidence in speaking Arabic. Therefore, this study aims to analyze the use of visual media in improving Arabic speaking skills among students at Syarifuddin Islamic Boarding School, Lumajang. This research employed a qualitative approach with a descriptive design. Data were collected through classroom observations, semi-structured interviews, and document analysis to obtain comprehensive insights into the implementation of visual media in Arabic language instruction as well as students’ responses to its use. The primary research participants were Arabic language teachers, while students functioned as supporting informants. Data analysis involved data reduction, data display, and conclusion drawing to ensure validity and accuracy. The findings show that the use of visual media, including pictures, instructional videos, and vocabulary cards, has a positive impact on students’ Arabic speaking skills. Visual media attract students’ attention, increase motivation and active participation, and help them understand vocabulary and sentence structures more easily. In addition, students demonstrate greater confidence, fluency, and willingness to express ideas orally in Arabic during learning activities. This study contributes to Arabic language education by offering an effective instructional alternative to enhance speaking skills. The results are expected to serve as a reference for educators in developing innovative, engaging, and sustainable Arabic learning practices in Islamic boarding schools in diverse educational contexts.